2012
DOI: 10.3727/096368911x605330
|View full text |Cite
|
Sign up to set email alerts
|

Liver Tissue Engineering Utilizing Hepatocytes Propagated in Mouse Livers in Vivo

Abstract: Recent advances in tissue engineering technologies have highlighted the ability to create functional liver systems using isolated hepatocytes in vivo. Considering the serious shortage of donor livers that can be used for hepatocyte isolation, it has remained imperative to establish a hepatocyte propagation protocol to provide highly efficient cell recovery allowing for subsequent tissue engineering procedures. Donor primary hepatocytes were isolated from human α-1 antitrypsin (hA1AT) transgenic mice and were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…Recently, a cell sheet-based tissue engineering approach has attracted much attention in cell transplantation therapy [13][14][15][16][17] because of its potential for delivering a large number of cells to the desired organ without loss of transplanted cells. A previous study has shown that the cell viability after islet cell sheet transplantation was higher than that after direct cell infusion [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a cell sheet-based tissue engineering approach has attracted much attention in cell transplantation therapy [13][14][15][16][17] because of its potential for delivering a large number of cells to the desired organ without loss of transplanted cells. A previous study has shown that the cell viability after islet cell sheet transplantation was higher than that after direct cell infusion [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it might be reasonable to expect that a cell sheet engineering approach would realize improvements in the control of engraftment efficiency and the avoidance of unexpected site engraftment of human iPS-HLCs. To date, several researchers have conducted hepatocyte sheet transplantation into ectopic sites (e.g., the subcutaneous space) and succeeded in achieving therapeutic values in experimental animal models [14][15][16]. However, the feasibility and therapeutic values of human iPS-HLC sheet transplantation on the liver surface (orthotropic transplantation) have yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiments in which normal mouse hepatocytes are transplanted to uPA/SCID mice, we identified that the propagated and then isolated hepatocytes can be propagated again in the uPA/SCID mice liver. Furthermore, we have succeeded in fabricating cell sheets composed of the hepatocytes propagated in the uPA/SCID liver [ 89 ]. Although there are certainly concerns about an ethical issue and a contamination of small amount of mice-derived components, the proposed method utilizing uPA/SCID mice is advantageous in terms of enabling researchers to keep stocks of the hepatocytes and provide the fresh cells any time on demand.…”
Section: Cell Sheet Technology As a Novel Therapeutic For Hemophiliamentioning
confidence: 99%
“…Hepatocyte phenotype depends on 3D conditions, as well as cell-cell and cell-extracellular matrix (ECM) interactions [15]. Recently, a cell sheet-based tissue engineering (TE) approach that improves engraftment efficiency and avoids unexpected site cell engraftments has been introduced [14,16,17]. Furthermore, multilayered hepatocyte sheets containing endothelial cells [18] or fibroblasts [19] improved hepatocyte functions by cell-cell interactions.…”
Section: Introductionmentioning
confidence: 99%